Influence of Enterprise Risk Management Success Factors on Firm Financial and Non-Financial Performance: A Proposed Model - Ahmed, Idris; Manab, Norlida Abdul (International Journal of Economics and Financial Issues, 2016)
Corporate scandals and the fall of world leading business organizations have triggered scholars and professionals to re-examine the link between risk management initiatives and the performance of business organizations. The objective of this paper is to propose a research framework that intend to examine the influence of Enterprise Risk Management (ERM) success factors on firm financial and non-financial performance. The factors are selected based on critical risk management issues affecting the Nigerian financial industry. The study will have practical implications to business leaders, regulatory agencies, rating agencies and government. Keywords: Enterprise Risk Management, ERM Success Factors, and Firm Performance JEL Classifications: G01, G31